Intrathoracic migration of a Kirschner wire - Özarslan, Fatma (Oxford University Press, 2014)
Kirschner (K) wires can easily migrate, resulting in serious complications. We report a 49-year-old woman who had a rare and late complication related to the migration of K wire. It had been used for left hip replacement 8 years ago. The patient admitted to our hospital with breathing-dependent chest pain and increasing dyspnea for ∼2 h. Chest X-ray and chest computed tomographic scans revealed the presence of a metallic image of ∼5–6 cm in the right hemithorax. There was a large hemothorax but no pneumothorax. A right thoracotomy was performed and the wire was removed without complications. Surprisingly, no injury was noted to any intervening abdominal structure intra-operatively. Patients, who are treated with K wire, should be informed of the risk of wire migration and should undergo regular postoperative follow-ups including radiography.